1999
DOI: 10.1038/sj.jhh.1000757
|View full text |Cite
|
Sign up to set email alerts
|

A randomised double-blind study comparing nifedipine GITS 20 mg and bendrofluazide 2.5 mg administered once daily in mild-to-moderate hypertension

Abstract: A multicentre, randomised, double-blind, parallel group comparison of nifedipine GITS 20 mg (Adalat ® LA) once daily and bendrofluazide 2.5 mg once daily in patients with mild-to-moderate hypertension was conducted. Two hundred patients with a diastolic blood pressure (BP) in the range 95 to 109 mm Hg were randomised to active treatment for 6 weeks. For the per-protocol efficacy population, both treatments resulted in clinically significant mean reductions of trough diastolic BP (nifedipine GITS −8.9 mm Hg, be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…However, much of this evidence is derived from studies in which CCBs were inappropriately prescribed and patients were inadequately monitored 21,22 . There is substantial evidence and there are ongoing studies to support the use of the long‐acting DHP CCBs, such as amlodipine, in a wide spectrum of hypertensive patients 23–28 …”
Section: Considerations For Antihypertensive Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…However, much of this evidence is derived from studies in which CCBs were inappropriately prescribed and patients were inadequately monitored 21,22 . There is substantial evidence and there are ongoing studies to support the use of the long‐acting DHP CCBs, such as amlodipine, in a wide spectrum of hypertensive patients 23–28 …”
Section: Considerations For Antihypertensive Therapymentioning
confidence: 99%
“…β‐blockers and diuretics are associated with metabolic effects that may offset the benefits of blood pressure reduction. These drugs may also have adverse effects on insulin resistance, contributing to the risk of developing diabetes 20–34 . In comparison, CCBs and ACE inhibitors are generally associated with neutral metabolic effects, although some studies have reported improvements in insulin sensitivity with ACE inhibitors 35–37 .…”
Section: Considerations For Antihypertensive Therapymentioning
confidence: 99%